2010
DOI: 10.3945/jn.109.109355
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Gene -308 G/A Polymorphism Modulates the Relationship between Dietary Fat Intake, Serum Lipids, and Obesity Risk in Black South African Women

Abstract: The prevalence of obesity and related disease risk is high in black South African (SA) women, possibly influenced by the dietary transition associated with urbanization. This study explored interactions between dietary fat intake and the tumor necrosis factor-alpha (TNFA) -308 G/A polymorphism on obesity, insulin resistance, and serum lipid concentrations in urbanized black SA women. Normal-weight (n = 105) and obese (n = 118) women underwent measurements of body composition, fat distribution, fasting serum li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 42 publications
7
41
0
1
Order By: Relevance
“…The methods used in this study have been described in detail previously. 1 In brief, basic anthropometric measurements, including weight, height and waist and hip circumferences were taken, and whole body composition was measured using dual-energy X-ray absorptiometry (Hologic Discovery-W, software version 12.1, Hologic Inc., Bedford, MA, USA). Abdominal visceral and subcutaneous adipose tissue areas were measured using computerized tomography (Toshiba Xpress Helical Scanner, Toshiba, Tokyo, Japan) at the level of L4-L5 lumbar vertebrae.…”
Section: Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods used in this study have been described in detail previously. 1 In brief, basic anthropometric measurements, including weight, height and waist and hip circumferences were taken, and whole body composition was measured using dual-energy X-ray absorptiometry (Hologic Discovery-W, software version 12.1, Hologic Inc., Bedford, MA, USA). Abdominal visceral and subcutaneous adipose tissue areas were measured using computerized tomography (Toshiba Xpress Helical Scanner, Toshiba, Tokyo, Japan) at the level of L4-L5 lumbar vertebrae.…”
Section: Measurementsmentioning
confidence: 99%
“…Studies from our laboratory, 1 and others [1][2][3] have shown that dietary fat intake modifies the relationship between the tumor necrosis factor-a gene (TNFA) -308 G4A polymorphism (rs1800629) and adiposity, and serum lipid concentrations. Common to all these studies was that the pro-inflammatory A allele of the functional TNFA-308 G4A polymorphism was associated with increased risk for obesity and dyslipidemia, and appeared to be more responsive to dietary fat intake.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations